Recurrence-Free Survival Stage IB1-IIA2 Intermediate Risk Group (Based on Kartu Delgado) Cervical Carcinoma after Radical Surgery and Adjuvant Radiotherapy - Friadi, Andi (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To evaluate the benefits of adjuvant radiotherapy (ART) based on Kartu Delgado (simple form of Gynecologic Oncology Group (GOG) scoring system) aimed at women with early stage cervical cancer after radical surgery. Method: Fifty patients were enrolled for this study. Twenty one patients from 2011-2012 were given ART following surgery based on their Kartu Delgado score from as follows: score 120 were given ART. Their score and recurrence were compared with 29 patients who were treated in 2009-2010 (based on single prognostic factor). Result: We observed eighteen recurrences for the duration this study. Thirteen patients from the period of 2009-2010 and five patients from the period of 2011-2012. Most recurrences occurred in patients from 2009-2010 with score > 120 but were not designated ART. Two-years recurrence-free survival (RFS) for subjects with score 120 with ART was 64.29%. Conclusion: Adjuvant radiotherapy given based on Kartu Delgado reduced the number of recurrences in women with stage IB-IIA cervical cancer after treated by surgery. [Indones J Obstet Gynecol 2014; 3: 146-152] Keywords: cervical carcinoma, intermediate risk, prognostic factor, radical hysterectomy